2008
DOI: 10.1007/s11250-008-9145-2
|View full text |Cite
|
Sign up to set email alerts
|

Serum enzymes levels and influencing factors in three indigenous Ethiopian goat breeds

Abstract: Serum enzymes were studied in 163 apparently healthy goats from three indigenous goat breeds of Ethiopia. The effect of breed, age, sex and season on alanine aminotransferase (ALT) / glutamic pyruvic transaminase (GPT), aspartate aminotransferase (AST) / glutamic oxalacetic transaminases (GOT), alkaline phosphatase (ALP) and acid phosphatase (AcP) levels was assessed. The mean serum enzymes levels of the indigenous Arsi-Bale, Central Highland and Long-eared Somali goat breeds ranged from 14.0-20.2 iu L(-1) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 13 publications
6
13
0
1
Order By: Relevance
“…The finding that ALP levels were higher in young goats compared to mature goats concurs with Antunovic et al (2004) who reported a decrease in ALP level with an increase in age of goats. Tibbo et al (2008) and Piccione et al (2010) had similar findings with Arsi-Bale goats of Ethiopia and Girgentana goats of Italy, respectively. In young growing animals, osseus ALP is the predominant form of serum ALP which diminishes as maturation progresses until the epishysis closes (Toba et al, 1992;Farver, 1997).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…The finding that ALP levels were higher in young goats compared to mature goats concurs with Antunovic et al (2004) who reported a decrease in ALP level with an increase in age of goats. Tibbo et al (2008) and Piccione et al (2010) had similar findings with Arsi-Bale goats of Ethiopia and Girgentana goats of Italy, respectively. In young growing animals, osseus ALP is the predominant form of serum ALP which diminishes as maturation progresses until the epishysis closes (Toba et al, 1992;Farver, 1997).…”
Section: Discussionmentioning
confidence: 54%
“…In addition, aspartate aminotransferases (AST), glutamyltransferase (GGT), alkaline phosphatase (ALP), and alanine aminotransferase (ALT), which are enzymes that are mostly produced by the liver (Smith and Sherman, 1994), are also predictive of the health status of goats (Otto et al, 2000;Ikhimioya and Imasuen, 2007;Pierce et al, 2007;Mahgoub et al, 2008). The information obtained from liver enzymes, blood minerals, and faecal egg counts substantiates the physical examination and, coupled with medical history, provides an excellent basis for estimation of severity of cases (Piccione et al, 2010) and treatment of goats (Tibbo et al, 2008). Although several studies have been conducted on blood parameter levels in goats (Pambu-Gollah et al, 2000;Kannan et al, 2003;Stella et al, 2007) and several others on the use of faecal egg counts (Hoste et al, 2005;Stella et al, 2007;Rumosa Gwaze et al, 2009a) in monitoring the health status of goats, none have been focused on the relationship between these parameters.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Young animals have relatively high levels of creatinine kinase which may be linked with susceptibility to stress-induced events such as capture and handling and capture myopathy [42]. Stress could affect transaminases activity in livestock animals [46]- [49], severe exercises (stressor) were reported to have resulted in an increase in these enzymes e.g. ALP and AST [50].…”
Section: The Influence Of Stress On Physiological Haematological Andmentioning
confidence: 99%
“…The ALAT is a transaminase enzyme present in high concentrations in the cytoplasm of hepatocytes (Kupczynski and Chudoba-Drozdowska 2002). The ALAT is considered one of the most sensitive enzymes in the diagnosis of hepatocellular injury (Tibbo et al 2008). In our study, the values for the plasma concentrations of γ-GT and ALAT were close to the value ranges (20−50 IU/l for γ-GT and 15.3−52.3 IU/l for ALAT, respectively) of Tibbo et al (2008) and Djuricic et al (2011).…”
Section: Plasma Lipid Profile and Enzymatic Activitiesmentioning
confidence: 99%